2010
DOI: 10.1111/j.1600-0714.2010.00926.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of polaprezinc on morphological change of the tongue in zinc-deficient rats

Abstract: OBJECTIVE: To examine the effects of polaprezinc on morphologic change of the tongue epithelium and on cell cycle regulation of taste bud cells by using zinc-deficient rats, an animal model of taste disturbance. METHODS: After 28 days of feeding with zinc-sufficient or -deficient diet, the rats fed a zinc-deficient diet were divided into four groups in which 0, 1, 3 and 10 mg ⁄ kg of polaprezinc were administered for 28 days with continuation of diet. Histopathological and morphological examinations of the ton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 19 publications
(22 reference statements)
0
10
0
Order By: Relevance
“…This suggests that serum zinc reflects dietary intake and nutritional status. It is well known that zinc deficiency causes dysgeusia [ 35 ], producing a vicious circle in which dysgeusia reduces appetite and causes further zinc deficiency. Zinc supplementation in patients with renal failure and hemodialysis has been reported to increase serum zinc levels, reduce the rate of protein catabolism, and improve malnutrition [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that serum zinc reflects dietary intake and nutritional status. It is well known that zinc deficiency causes dysgeusia [ 35 ], producing a vicious circle in which dysgeusia reduces appetite and causes further zinc deficiency. Zinc supplementation in patients with renal failure and hemodialysis has been reported to increase serum zinc levels, reduce the rate of protein catabolism, and improve malnutrition [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Frailty may develop under conditions of deficiency in various nutrients, including calcium, zinc, albumin, and protein, which is associated with the onset of osteoporosis and sarcopenia. Hypozincemia is related to appetite loss ( 6 ), depression ( 7 ), and taste abnormality ( 8 ), and these symptoms are risk factors for hypoalimentation. Semba et al reported that frail women had lower serum concentrations of zinc at baseline than women who were not frail ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Adebusoye et al reported that constipation and oral problems were significantly associated with undernutrition in a cross-sectional study of older persons ( 5 ), so malnutrition and frailty may be caused by constipation and upper abdominal symptoms, such as heartburn, regurgitation, and epigastric discomfort. Taste disorder, depression, and appetite loss may be associated with the aging process; however, in later years, these symptoms may be related to hypozincemia ( 6 - 8 ). Zinc is involved in in vivo enzyme activation, and the physiological functions of zinc include roles in skin metabolism, the generative function, maintenance of taste, mental function, and immunity ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Zinc deficiency secondary to any etiology leads to taste disturbances; thus, zinc depletion is corrected for patients presenting with taste imbalances [ 4 – 7 ]. It has been observed in vivo that zinc administration improves decreased taste bud cell proliferation caused by zinc deficiency [ 8 ]. Zinc administration improves taste in 50–82% of patients suffering from taste disorders [ 9 ].…”
Section: Introductionmentioning
confidence: 99%